Peran Literasi Spiritual Digital dalam Pembentukan Akhlak Profesional Mahasiswa Vokasi - Afip Miftahul Basar; Ceceng Saepulmilah (Arfah BHMS Foundation, 2026)
The rapid integration of digital technology in vocational education presents both opportunities and challenges in shaping students’ character and professional ethics. This study aims to examine the role of digital spiritual literacy in fostering professional morality among vocational students in the Mineral Chemical Engineering program at the Morowali Metal Industry Polytechnic, particularly within the Religious Education and Ethics course. A quantitative approach with a correlational survey design was employed. Data were collected from 87 students using a Likert-scale questionnaire and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results reveal that digital spiritual literacy has a positive and significant effect on students’ professional morality (β = 0.56; p < 0.001), with a moderate explanatory power (R² = 0.31). These findings indicate that integrating spiritual awareness and Islamic ethical values into digital learning practices plays a crucial role in strengthening integrity, responsibility, discipline, and ethical communication among vocational students. This study contributes to the literature on Islamic education and vocational education by highlighting digital spiritual literacy as a strategic approach to developing professional character aligned with the demands of the industrial sector.